Method for producing oxide-based ceramic matrix composite material using zirconia continuous fiber as reinforcing fiber
Patent Information
- Application Number
- JP2022100201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-22
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-06-22
AI Technical Summary
Existing ceramic matrix composite materials, such as SiC/SiC and alumina matrix/alumina fiber composites, are limited by high-temperature strength and environmental resistance, making them unsuitable for gas turbines with combustion temperatures above 1400°C without cooling, and there is a need for materials that can withstand temperatures between 1700°C to 1800°C.
A method involving the production of a zirconia-based ceramic matrix composite material using zirconia continuous fibers with a carbon interface layer, where zirconia continuous fibers are coated with BaZrO3 and impregnated with a zirconia ceramic matrix, enhancing heat and environmental resistance through a multi-step process including slurry preparation, impregnation, drying, and secondary firing.
The resulting composite material exhibits higher maximum usable temperature and toughness, suitable for gas turbines with combustion temperatures up to 1800°C, maintaining strength and environmental resistance without the need for cooling.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an oxide-based ceramic matrix composite material, and more particularly to a method for producing a composite material having excellent heat resistance and environmental resistance, which has a matrix of zirconia-based ceramics reinforced with improved highly heat-resistant zirconia continuous fibers. [Background technology]
[0002] Regarding energy supply and demand, rising energy prices have led to calls for the renewal of power generation facilities to improve thermal efficiency. In particular, in Japan, the suspension of nuclear power plants due to the Great East Japan Earthquake has necessitated the expansion of thermal power plants and power generation facilities using natural energy as alternative energy measures, and renewal of power generation facilities to improve thermal efficiency has become economically rational. Furthermore, as seen in the Kyoto Protocol, reduction of carbon dioxide emissions is required from the standpoint of global environmental conservation.
[0003] In response to societal demand for improving the thermal efficiency of such power generation facilities and reducing carbon dioxide emissions, for example, gas turbine combined cycle power generation is expected to see long-term market expansion as the cleanest and most economical thermal power generation facility that can coexist with natural energy and nuclear power generation. Thus, micro gas turbines began to be introduced as distributed power sources in the 1990s, and many manufacturers have since entered the market. Many of their advantages are recognized, including their simple structure, excellent load fluctuation characteristics, easy maintenance, and small impact on the environment. However, unlike large gas turbines for power generation, the inside of the turbine cannot be cooled, so the combustor outlet temperature is low, and power generation efficiency is low at a maximum of about 28%, so the market size has not expanded. In this situation, ceramic matrix composites (CMCs) have already been put to practical use in jet engines as materials that meet the above demands, such as SiC fiber-reinforced SiC matrix CMCs, and have achieved significant improvements in fuel efficiency. This material has good high-temperature strength, but has limited environmental resistance (oxidization), so its maximum usable temperature is limited to around 1300°C. On the other hand, alumina matrix / alumina fiber composite materials have been put to practical use as oxide-based CMCs with excellent environmental resistance, but due to their low high-temperature strength, their usable temperature is even lower than that of SiC / SiC composite materials, and there was an issue that they could not be used for the targeted applications.
[0004] For example, as described in Non-Patent Document 1, "When a 1700°C class gas turbine is put into practical use as the main engine of a combined cycle power generation facility, the power generation efficiency will exceed 62% (low heating value basis), which will be a significant improvement over conventional thermal power generation facilities. For example, assuming that the thermal efficiency of a 1.25 million kW coal-fired power generation facility is 44% (low heating value basis), the annual CO 2 The amount of emissions will be 8.53 million tons. If this is replaced with a natural gas-fired 1700°C class combined cycle power plant, the amount of CO 2 The total CO2 emissions will be 3.24 million tons, a 62% reduction.' Therefore, it is of great significance to develop heat-resistant materials that can be used in natural gas-fired 1700℃-class combined cycle power generation facilities.
[0005] In view of this situation, metallic materials are used as the turbine blades and vanes of 1700°C-class gas turbines for power generation turbine engines, but since the combustion temperature itself is above the melting point of the metallic materials, it is necessary to lower the material temperature by cooling with air, steam, etc. However, since the material temperature still reaches a maximum of about 900°C, properties such as creep strength, toughness, thermal fatigue properties, high cycle fatigue properties, oxidation resistance, and corrosion resistance are required. Furthermore, in gas turbines with a combustion temperature of 1800°C, the metal temperature will continue to rise even if cooling is performed, so creep strength, toughness, and oxidation resistance are the most fundamentally important properties. In conventional 1500°C-class gas turbines, in order to simultaneously provide creep strength and toughness, a ductile / brittle dual-phase material is used that combines a solid solution phase with high ductility and toughness with an intermetallic compound phase with excellent high-temperature strength. Ni-base superalloys are a typical example and one of the most excellent heat-resistant materials. However, in order to use Ni-base superalloys in 1800°C-class gas turbines, the material temperature must be significantly lowered from 1800°C by extreme cooling. This causes a large amount of energy loss, and there is a problem that the targeted efficiency improvement cannot be achieved. Therefore, materials that do not require this cooling or that have the strength and environmental resistance at ultra-high temperatures and require only minor cooling are required for gas turbines with combustion temperatures of 1700°C to 1800°C.
[0006] Among the ceramic matrix composites (CMCs), SiC fiber / SiC matrix composites are heat-resistant materials that have attracted attention as materials that can be used at high temperatures that are difficult for metals to handle. As mentioned above, the so-called SiC / SiC composites have been put to practical use in jet engines and have achieved significant improvements in fuel efficiency. However, although this SiC / SiC composite has high high-temperature strength, it has limitations in its environmental resistance and oxidation easily progresses at ultra-high temperatures, so that the maximum usable temperature has been considered to be around 1400°C. In other words, it has been unsuitable as a material that can be used without cooling or with only slight cooling in gas turbines with the target combustion temperatures of 1700°C to 1800°C. On the other hand, oxide ceramics are materials that are inherently excellent in environmental resistance at ultra-high temperatures. In other words, since the oxides are already oxidized, the oxidation will not progress any further. As a ceramic matrix composite material based on this oxide, for example, there is one in which an alumina matrix is impregnated between two-dimensionally woven mullite fibers, as proposed by the present applicant, as disclosed in Patent Document 1. However, although this material has good environmental resistance (oxidation resistance), its strength at high temperatures is insufficient, and its heat resistance temperature is limited to about 1100°C.
[0007] Zirconia is known as an oxide material with high high-temperature strength. In addition, Patent Document 2 proposes an oxide-based ceramic fiber / oxide-based ceramic composite material, proposing zirconia as the metal oxide that is the main component of the ceramic fiber. However, only an abstract list of gas turbine engine-related components, which is the application, is given, and no material that can withstand use in gas turbines with combustion temperatures of 1700°C to 1800°C is presented. Therefore, the present inventors have conducted extensive research to solve the above-mentioned problems. That is, the purpose of the research is to provide a ceramic matrix composite material used in gas turbines with a combustion temperature of 1700°C to 1800°C, in which a ceramic matrix having high heat resistance and environmental resistance is reinforced with ceramic fibers having similarly high heat resistance and environmental resistance. The inventors have provided stabilized zirconia continuous fibers or partially stabilized zirconia continuous fibers that can be used in zirconia fiber-reinforced zirconia composite materials, and a manufacturing method thereof (Patent Document 3), and further proposed a manufacturing method for a composite material having a zirconia-based matrix using the fibers (Patent Document 4). According to this manufacturing method for a ceramic matrix composite material, a zirconia continuous fiber / BaZrO 3 It is possible to manufacture matrix composite materials, which are said to be capable of withstanding combustion temperatures of 1700°C to 1800°C class gas turbines.
[0008] However, the properties that were actually evaluated were the oxidation resistance evaluated based on the external shape retention and weight change in an ultra-high temperature atmospheric oxidation test, and the compressive strength at 1800°C, and the mechanical properties of the composite material itself were not evaluated. In the first place, this composite material has a large diameter of the fibers used as reinforcing materials and is poorly processable into woven fabrics, so the strength of the composite material itself cannot be expected, and it was developed to be attached to ceramic, glass ceramic, or carbon structures and used as a composite structure. Therefore, there was an issue that the composite material itself was not a material that could withstand use in gas turbines with combustion temperatures of 1700°C to 1800°C. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO2012 / 077787A1 [Patent Document 2] JP 2002-173376 A [Patent Document 3] Patent No. 6238286 [Patent Document 4] Patent No. 6327512 [Non-patent literature]
[0010] [Non-Patent Document 1] Mitsubishi Heavy Industries Technical Review Vol. 47 (2010) No. 1, pp. 25-30 Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, the present invention aims to solve the above-mentioned problems, and relates to a ceramic matrix composite material having a higher maximum usable temperature than SiC / SiC composite material, and aims to provide a manufacturing method for a high-toughness, high-strength ceramic matrix composite material in which a ceramic matrix having high heat resistance and environmental resistance is reinforced with ceramic fibers having similarly high heat resistance and environmental resistance. Here, although SiC / SiC composite materials have high high-temperature strength, they have limitations in environmental resistance and oxidation easily proceeds at ultra-high temperatures, so that the maximum usable temperature has been set to about 1400°C. [Means for solving the problem]
[0012] The method for producing the ceramic matrix composite material of the present invention includes, for example, a first step of providing at least one of a fiber bundle, a two-dimensional fabric, and a three-dimensional fabric, each of which is made of zirconia continuous fibers coated with carbon, as shown in FIG. 1; 3a second step of preparing a slurry by mixing a powder or a zirconia-based ceramic powder with water or a solution in which a zirconia-based ceramic precursor is dissolved in an organic solvent in a predetermined ratio; a third step of preparing a prepreg by applying or impregnating the fiber bundle, two-dimensional fabric, or three-dimensional fabric with the slurry; a fourth step of removing water or an organic solvent while adding further slurry or precursor solution to the prepreg as necessary, and drying or gelling the prepreg and then drying; a fifth step of primarily firing the prepreg from room temperature to a predetermined temperature at a predetermined heating rate in a non-oxidizing atmosphere to prepare a preform, and after firing, further impregnating the preform with the precursor solution, gelling the preform, and repeating the firing again to densify the preform; and a sixth step of secondary firing in the air or in a non-oxidizing atmosphere as necessary, with the temperature at which the composite material will be used set as the maximum heating temperature.
[0013] The method for producing a ceramic matrix composite material of the present invention is a method for producing a ceramic matrix composite material in which a ceramic matrix made of a material with high heat resistance and environmental resistance, i.e., a zirconia-based ceramic matrix, is reinforced with zirconia-based continuous fibers with similar high heat resistance and environmental resistance coated with carbon, and the composite material has high toughness and strength due to the function of the carbon interface layer. The ceramic matrix is BaZrO 3 Alternatively, the present invention is characterized in that it is made of zirconia ceramics and uses zirconia continuous fibers having improved heat resistance as the reinforcing material. In the method for producing a ceramic matrix composite material of the present invention, preferably, 3 The zirconia-based ceramic powder is a fine powder having an average particle size of about 1 μm or less, and stabilized or partially stabilized zirconia is preferable. Furthermore, it is desirable to impregnate these fine powders with a precursor polymer synthesized by co-hydrolysis and condensation of metal oxides such as zirconia and yttria, which produce stabilized zirconia upon firing, since this promotes sintering after firing. At the temperatures at which the ceramic matrix composite material of the present invention is used, the carbon interface layer is burned off in the secondary firing, and the gap interface layer functions to maintain high toughness. Effect of the Invention
[0014] According to the method for producing a ceramic matrix composite material of the present invention, the zirconia continuous fiber / BaZrO 3 It is possible to produce a ceramic matrix composite material or a zirconia continuous fiber / zirconia matrix composite material. The produced ceramic matrix composite material is suitable as a high-toughness, high-strength composite material with a higher maximum usable temperature than SiC / SiC composite materials, which have a maximum usable temperature of about 1400°C. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a flow chart illustrating the method for producing a ceramic matrix composite material according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram of an apparatus for carrying out the hexane bubble flow method for coating fibers with carbon. [Diagram 3] FIG. 3 is an SEM photograph of a cross section of the fiber showing the thickness of the carbon coating. [Figure 4] Figure 4 shows the stress-strain curve of the bending test of the 1D-CMC CMC(ZB)-5, which shows that fiber pull-out occurs at the time of failure. [Diagram 5] Figure 5 shows SEM photographs showing fiber pullout at the forced fracture surface of the 1D-CMC CMC(ZB)-5 after bending test. [Figure 6] Figure 6 shows the SEM photographs of the forced fracture surface of the 1D-CMC CMC(ZB)-15, which shows the formation of a gap interfacial layer between the fiber and the matrix. [Figure 7] Figure 7 shows the SEM photographs of the forced fracture surface of the 1D-CMC CMC(ZB)-15, which shows the formation of a gap interfacial layer between the fiber and the matrix. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be specifically described below. Note that the use of "to" to indicate a numerical range indicates a numerical range between a lower limit and an upper limit, and in this specification, unless otherwise specified, it indicates a range between the lower limit and the upper limit. FIG. 1 is a flow chart for explaining the method of producing an oxide-based ceramic matrix composite material using zirconia continuous fibers as reinforcing fibers according to the present invention. As the ceramic matrix composite material, a zirconia continuous fiber / BaZrO 3 A method for making a composite material consisting of a matrix and continuous zirconia fiber / zirconia-based ceramic is described.
[0017] First, a zirconia continuous fiber bundle, or a two-dimensional fabric obtained by weaving a zirconia continuous fiber bundle two-dimensionally, or a three-dimensional fabric obtained by weaving a zirconia continuous fiber bundle three-dimensionally is prepared (S102), and then the zirconia continuous fiber bundle, woven fabric, or three-dimensional fabric is coated with carbon (S104, first step). This zirconia fiber bundle, two-dimensional fabric, or three-dimensional fabric can be produced by bundling a predetermined number of zirconia continuous fiber bundles, or by weaving them using existing technology. The volume fraction V of zirconia fiber in the composite material is f , or mass content M f can be controlled to 40% or less of the apparent total volume or total mass (fiber + matrix) of the composite material produced. The average diameter of the zirconia continuous fibers is, for example, about 10 to 20 μm. The procedure for producing the zirconia continuous fibers with improved heat resistance will be described later.
[0018] Next, BaZrO 3 Alternatively, a slurry containing fine zirconia ceramic particles in a predetermined ratio is prepared (S106, second step). 3is a fine powder having an average particle size of about 1 μm or less, and the zirconia-based ceramic powder is also a fine powder having an average particle size of about 1 μm or less, and stabilized or partially stabilized zirconia is preferable. The dispersion medium for preparing the slurry may be water or an aqueous solution in which about 3% by weight of polyvinyl alcohol is dissolved, or an organic solvent such as acetone or xylene, but in order to reduce the porosity in the composite prepreg in the subsequent steps and to promote sintering between the fine particles used, it is preferable to use a solution in which a precursor polymer synthesized by co-hydrolysis and condensation of metal alkoxides such as zirconia and yttria, which produce stabilized zirconia by firing, is dissolved in an organic solvent. BaZrO in slurry 3 Alternatively, the concentration of the zirconia ceramic powder is preferably 50% by weight or more and 80% by weight or less, so that the slurry viscosity does not become too high and the fiber bundle can be efficiently impregnated with the powder. If the concentration is less than 50% by weight, the porosity of the matrix becomes too high, which is not preferable. When using a precursor solution, the precursor concentration is preferably 40% by weight or more and 70% by weight or less, since the slurry viscosity does not become too high. If it is about 70% by weight or more, the viscosity becomes too high and gelation may occur, which is not preferable. If it is 40% by weight or less, the matrix cannot be densified efficiently.
[0019] Next, the slurry prepared in the second step is applied to the zirconia continuous fiber bundle, two-dimensional fabric, or three-dimensional fabric carbon-coated in the first step to impregnate the fabric (S108, third step). If the zirconia fiber surface is water-repellent to the slurry containing water as a dispersion medium, the fabric can be first impregnated with a hydrophilic and highly volatile solvent such as acetone or methanol and then dried to suppress the water-repellency. This application and impregnation step can be efficiently performed by a known bagging method or pressure method. That is, the bagging method can be used in which a fiber bundle, two-dimensional fabric, or three-dimensional fabric coated with slurry is placed in a bag, vacuumed to remove the solvent, and then more slurry is added and the vacuuming is repeated; or, when using fiber bundles or two-dimensional fabrics, the drawing method can be used in which a fiber bundle coated with or impregnated with slurry is drawn into a tube of a specified shape and molded while pressurizing to remove the solvent; and, in the case of two-dimensional fabrics, the pressure method can be used in which a specified number of two-dimensional fabrics coated with or impregnated with slurry are stacked, sandwiched between stainless steel tubes, and pressure is applied to mold.
[0020] Next, the molded body impregnated with the slurry in the third step is dried, and further, if a precursor solution is mixed in the impregnation solution, the precursor may be gelled and decomposed by heating in a steam atmosphere to volatilize the organic components generated (S110, fourth step). The fourth step of removing water or organic solvent from the dried prepreg and drying or gelling and drying may be repeated after drying the prepreg or drying in a steam atmosphere, and further impregnating the prepreg with the precursor solution as necessary, removing water or organic solvent, and drying or gelling and drying. That is, by repeating this step, the number of times of the impregnation and firing process of the precursor solution in the fifth step can be reduced. The number of times of this additional impregnation is preferably from 1 to 4 times, and even if it is repeated 5 times or more, the precursor is not ceramicized, so the number of pores in the prepreg is extremely reduced, and the effect of densifying the matrix cannot be obtained. The heat treatment temperature is preferably 60°C or higher and 150°C or lower. The water vapor atmosphere is achieved by placing the prepreg on a water bath during heat treatment and performing heat treatment for a specified period of time. Although it depends on the temperature, a holding time of 1 hour or higher and 10 hours or lower is sufficient.
[0021] Next, the prepreg obtained in the fourth step is subjected to primary firing in an inert gas atmosphere at 1000°C to 1500°C (S112, fifth step). The primary firing is a step of sintering the matrix while leaving the carbon interface layer, and the atmosphere is preferably a nitrogen gas, argon gas, or vacuum atmosphere. Argon gas is particularly suitable because there is no possibility of nitride formation. The obtained composite material is called a preform, and the porosity may be 50% or more. Therefore, in order to further reduce the porosity, the process of impregnating the preform with a precursor solution, gelling, and drying is repeated three or more times, and the polymer impregnation and firing process, which involves primary firing, is repeated two or more times to densify the preform. The precursor solution is preferably one having a precursor concentration of 40% by weight or more and 70% by weight or less, since the slurry viscosity does not become too high and the material can be efficiently impregnated. If the precursor concentration is 70% by weight or more, the viscosity becomes too high and gelation may occur, which is not preferable. If the precursor concentration is 40% by weight or less, the matrix cannot be efficiently densified.
[0022] Next, the composite material obtained in the fifth step is finally sintered in air or a non-oxidizing atmosphere, if necessary, with the temperature at which the composite material will be used as the maximum heating temperature (S114, sixth step). This step may be carried out in the environment in which the composite material will actually be used, and is a step in which the composite material is finally sintered with the temperature at which the composite material will be used as the maximum heating temperature, in which the composite material is sintered in air to burn off the carbon layer that is the interface layer, and the resulting gap between the fiber surface and the matrix functions as the interface layer. The maximum heating temperature is preferably 1400°C or higher and 1600°C or lower. Temperatures higher than 1600°C are not preferred because they reduce the properties of the composite material.
[0023] FIG. 2 is a schematic diagram of an apparatus for carrying out the hexane bubble flow method for coating fibers with carbon. In the figure, nitrogen gas or argon gas is sent from a gas supply port 10 to a reaction chamber 24 and exhausted from a gas exhaust port 28. Gas flow meters 12a and 12b measure the flow rate of gas sent to the gas supply port 10, one gas flow meter 12a measures the flow rate of gas not containing an organic solvent, and the other gas flow meter 12b measures the flow rate of gas containing an organic solvent. A test tube 14 contains an organic solvent 16 and allows the gas passing through the gas flow meter 12b to contain an organic solvent gas. An example of the organic solvent that can be used is hexane, but is not limited to this. A cock 18 is opened when a gas containing an organic solvent is sent to the reaction chamber 24, and closed when it is not sent.
[0024] The temperature controller 20 controls the temperature inside the tubular heating furnace 22. The tubular heating furnace 22 heats and maintains the temperature of the reaction chamber 24 at a firing temperature of the fibers 26 selected from a zirconia continuous fiber bundle, a two-dimensional fabric, or a three-dimensional fabric. The ceramic matrix composite material thus prepared is evaluated for its oxidation resistance and high-temperature strength.
[0025] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Example 1 In the first step, a predetermined amount of ethyl 3-oxobutanoate is mixed with a predetermined amount of zirconium tetra-n-butoxide. After the exothermic reaction is completed, a predetermined amount of H 2 O was diluted with 2-propanol and mixed. After the exothermic reaction was completed, a 2-propanol solution of yttrium tri-n-butoxide or erbium acetylacetonate was added to ZrO 2 For Y 2 O 3 or Er 2 O 3The calculated amounts were mixed so that the amount of the metal oxide was a predetermined mole percent, and the mixture was stirred for 15 minutes. Then, the raw material alkoxide of the metal oxide, which is the crystallization inhibitor, aluminum ethyl acetoacetate diisopropylate, tetraethoxysilane, and tetra-i-propoxy titanium were added in predetermined amounts, and further, a predetermined amount of H 2 O was diluted with 2-propanol and mixed. After the exothermic reaction was completed, the reaction was continued by gradually heating from room temperature in a water bath using a rotary evaporator to remove low-boiling components such as the solvent and hydrolysis product 2-propanol, and the mixture was concentrated to 95°C to obtain an yttria- or erbia-stabilized zirconia fiber precursor.
[0026] In the second step, the precursor obtained in the first step was put into a spinning tube as a xylene solution of a predetermined concentration, optionally with the addition of polycarbosilane (PCS), and the inside of the spinning tube was pressurized to approximately 2.5 MPa or less with nitrogen gas at a temperature at which the precursor solution was extruded with an appropriate viscosity, and the precursor was extruded from a nozzle with a diameter of 100 μm while being continuously wound up at a speed of approximately 1,800 m / min. In the third step, the obtained raw fiber was heated in saturated steam from 45 to 200°C at a rate of 10°C / hour and held for 1 hour to make it infusible. The infusibility was confirmed by the fact that it did not melt on a hot plate at 150°C.
[0027] In the fourth step, the infusible fibers were heated to 1000°C at a rate of 100-200°C / hour in air, inert atmosphere, or inert gas containing water at saturated vapor pressure at room temperature, and then held for 1 hour for low-temperature firing, i.e., primary firing. The inert gas containing water at saturated vapor pressure was prepared by bubbling Ar gas into water at room temperature and then introducing it into a firing furnace. White fibers were obtained from the fibers fired in air, while black fibers were obtained from the fibers fired in an inert atmosphere or inert gas containing water at saturated vapor pressure at room temperature, and carbon analysis showed that the fibers contained less than 6% carbon. The fiber diameter was approximately 6-20 μm. Table 1 shows the composition of the synthesized fiber precursors, the fiber manufacturing conditions, and the fiber properties. The three digits following the "-" of the precursor are the synthesis lot numbers. There are precursors with the same composition, but as shown in Table 1, the synthesis conditions are different, so the different synthesis lots are noted. The notation of the synthesis lot numbers is the same in Tables 2 and 3.
[0028] [Table 1]
[0029] Using these fibers, rod-shaped one-dimensional reinforced composite materials with a diameter of about 2 mm and a length of approximately 10 mm were produced using the process shown in Figure 1. First, using the apparatus shown in Figure 2, each fiber bundle in Table 1 was heated to 1000°C at 200°C / hour by the hexane bubble flow method while introducing Ar gas containing hexane vapor into the annular furnace cavity in which the fiber bundle was placed, and held for 0.5 hours to coat the fiber surface with carbon. Figure 3 shows an SEM photograph of the cross section of the fiber, indicating the thickness of the coating. Next, the impregnation slurry was prepared. First, BaZrO 3 or 8 mol% Y 2 O 3 Stabilized ZrO 2 The (8YSZ) fine powder was mixed with 3 wt% polyvinyl alcohol (PVA) aqueous solution to prepare a slurry of 75 wt%. 3 The slurry was prepared by dissolving the precursor Zr-Y(0.1)-077 (shown in Table 1) in xylene at 50 wt%. 3 The fine powder concentration was adjusted to 75 wt %.
[0030] Next, the prepared slurry was applied or impregnated to a specified amount of fiber bundle in Table 1, and the bundle was molded by drawing it into an alumina tube with an inner diameter of 2 mm and a length of 100 mm while removing excess solvent and slurry. After molding, the bundle was dried at 85°C for 5 to 10 hours, and then vacuum-impregnated with a 50 wt% xylene solution of the precursor Zr-Y(0.1)-077 and dried at 85°C for 0.5 hours to produce a round bar prepreg. Next, these prepregs were heated in an Ar gas atmosphere to 1000°C at 100°C / hour and held for 1 hour for primary firing. After firing, they were taken out of the alumina tubes to prepare preforms.
[0031] Next, 5 mol% Y 2 O 3 A 65wt% xylene solution of the precursor Zr-Y(0.1)-077, which is a 5YSZ precursor polymer synthesized by molecular design to contain, was prepared, and the resulting preform was vacuum impregnated, dried at 85°C for 0.5 hours, and the impregnated precursor was gelled in a saturated water vapor atmosphere at 85°C, and then dried at 85°C for 0.5 hours. This process was repeated four times, and then heated to 1000°C at 200°C / hour in an Ar atmosphere and held for 1 hour for additional primary firing. The resulting preform was further subjected to the PIP (Polymer Impregnation and Pyrolysis) method, which involves impregnation and firing of this precursor, to produce a one-dimensionally reinforced CMC mini-composite (1D-CMC).
[0032] Table 2 shows the fiber volume content and room temperature bending strength of the 1D-CMC manufactured under the above manufacturing conditions. ZB and YSZ of CMC(ZB) and CMC(YSZ) are the BaZrO 3 and 8 mol% Y 2 O 3 Stabilized ZrO 2 (8YSZ). The maximum room temperature bending strength was 199 MPa. Figure 4 shows the stress-strain curve of the bending test of CMC(ZB)-5. From this stress-strain curve, it was found that the manufactured 1D-CMC did not show brittle fracture. Also, referring to Figure 5, fiber pull-out was observed on the fracture surface, confirming that the interface layer was functioning adequately. [Table 2]
[0033] Table 3 shows the results of tensile tests at room temperature for 1D-CMC. CMC(ZB)-31, which had the smallest porosity, achieved a tensile strength of 175.3 MPa. Fiber pull-out was observed on the forced fracture surface in all cases, confirming that the interfacial layer was functioning. [Table 3]
[0034] Example 2 As in Example 1, 1D-CMC manufactured using fibers manufactured from Zr-Y(0.1)-077+PCS(0.05) precursor was treated at high temperature (corresponding to secondary firing) and then subjected to bending test at room temperature. For the high temperature treatment, the temperature was raised to 1500°C at 300°C / h in a specified atmosphere and held for 1 hour. The results of the bending test at room temperature of the 1D-CMC after the treatment are shown in Table 4. CMC(ZB)-32 showed a bending strength of 252 MPa, confirming the effect of improving strength due to the reduction in porosity and the promotion of densification by sintering the matrix in the secondary firing. Figure 6 shows an SEM photograph of the forced fracture surface of CMC(ZB)-15. From this figure, it was found that the carbon interface layer was burned away by firing in air, and a gap was formed between the fiber and the matrix, and this gap acted as an interface layer to cause the fiber to pull out.
[0035] [Table 4]
[0036] Example 3 Using fibers that had been made from a Zr-Y(0.1)-077+PCS(0.05) precursor and had been subjected to a secondary firing at 1300°C in air, a fiber bundle consisting of approximately 250 filaments was first carbon-coated in the same manner as in Example 1, and this was made into a plain weave fabric. After that, a two-dimensional reinforced CMC (2D-CMC) was produced using a process similar to that of Example 1. First, the impregnation slurry was prepared. The fine powder for the slurry was BaZrO 3 or 8 mol% Y 2 O 3 Stabilized ZrO 2 (8YSZ) and BaZrO 3 The slurry was prepared using a 50 wt % solution of the precursor Zr-Y(0.1)-077 in xylene.
[0037] Next, the woven fabric was cut into a size of about 65 mm x 65 mm, and the prepared slurry was applied or impregnated thereto, and three sheets were laminated, and the excess solvent was removed by the bagging method, and the sheets were sandwiched between SUS plates and pressed and fixed to form a prepreg. The prepreg was heated to 1200 ° C. in a vacuum at 200 ° C. / hour, and held at 1200 ° C. for 1 hour to produce a preform. The obtained preform was impregnated with the precursor solution, dried, steam-treated, and dried four times, and then primary-fired (PIP-treated) at 1200 ° C. Thus, 2D-CMC was produced. A photograph of the appearance of the obtained 2D-CMC is shown in FIG. 7. The thicknesses of the 2D-CMC (YSZ) and 2D-CMC (ZB) were 2.0 mm and 2.8 mm, respectively. The heat resistance of these two types of 2D-CMC was evaluated by erosion testing using an erosion testing machine manufactured by Ishikawajima-Harima Heavy Industries Co., Ltd., with DC arc heating (20 kW), a nozzle diameter of 75 mm, and a test temperature of 1800°C for 180 seconds.
[0038] The properties and erosion test results of each CMC are shown in Table 5. There was almost no deformation in any of them, and the mass change was very small, indicating excellent heat resistance. The thickness change was particularly small in 2D-CMC (YSZ), and even though the test temperature was very high at 1800°C, the wear rate was 9.7×10-5mm / sec, indicating high erosion properties. [Table 5] [Industrial Applicability]
[0039] According to the method for producing a ceramic matrix composite material of the present invention, a zirconia continuous fiber reinforced / zirconia-based ceramic matrix composite material can be produced. This oxide-based composite material is suitable as a gas turbine material capable of withstanding combustion temperatures higher than those of conventional SiC / SiC composite materials. [Explanation of symbols]
[0040] 10 Gas supply port 12a, 12b Gas flow meter 14 Test Tube 16 Organic solvent (Hexane) 18 Cook 20 Temperature Controller 22 Tubular heating furnace 24 Reaction chamber 26 Textiles 28 Gas exhaust port
Claims
1. A first step of providing at least one of a fiber bundle, a two-dimensional fabric, and a three-dimensional fabric, which is made of a zirconia continuous fiber coated with carbon; Fine grain BaZrO 3 a second step of preparing a slurry by mixing the powder or the zirconia-based ceramic powder with water or a precursor solution obtained by dissolving a zirconia-based ceramic precursor in an organic solvent in a predetermined ratio; A third step of coating or impregnating at least one of the fiber bundle, the two-dimensional fabric, and the three-dimensional fabric with the slurry to prepare a prepreg; A fourth step of drying or gelling the prepreg and then drying it; A fifth step of firing the preform from room temperature to a predetermined temperature at a predetermined heating rate in a non-oxidizing atmosphere, impregnating the preform with the precursor solution after firing, gelling the preform, and firing the preform again to densify the preform; The present invention relates to a method for producing an oxide-based ceramic matrix composite material having zirconia continuous fibers as reinforcing fibers.
2. 2. The method for producing a ceramic matrix composite material according to claim 1, wherein in the fourth step, at least one of water and an organic solvent is removed while the slurry or the precursor solution is further added to the prepreg, and drying or gelling is performed and then drying is performed.
3. 2. The method for producing a ceramic matrix composite material according to claim 1, further comprising a sixth step of final sintering in air or a non-oxidizing atmosphere at a maximum heating temperature equal to a temperature at which the composite material will be used.
4. The slurry is BaZrO 3 or stabilized or partially stabilized ZrO 2 The method for producing a ceramic matrix composite material according to claim 1, characterized in that small particles having an average particle size of submicrons or less are made into a slurry state using water or the precursor solution, and the slurry is impregnated into at least one of the fiber bundle, the two-dimensional fabric, and the three-dimensional fabric, and then sintered.
5. In the third step, The prepreg is a prepreg (unidirectional reinforced composite material) in which the fiber axes in the ceramic fiber aggregate after composite formation by converging the fiber bundles to which the slurry has been applied are continuous in one direction; A prepreg (two-dimensional reinforced composite material) in which fiber axes are arranged in a two-dimensional direction using a woven fabric coated with the slurry, or The slurry is applied to a three-dimensional woven fabric to produce a prepreg (three-dimensional reinforced composite material) with fiber axes aligned in three dimensions. The method for producing a ceramic matrix composite material according to claim 1 .
6. 2. The method for producing a ceramic matrix composite material according to claim 1, wherein the fifth step comprises firing the prepreg obtained in the fourth step from room temperature to a predetermined temperature at a predetermined heating rate in a non-oxidizing atmosphere to obtain a preform, and then repeating a process of impregnating the prepreg with a precursor solution, gelling, and drying three or more times, and then firing the preform, thereby densifying the preform two or more times.
7. 7. An oxide-based ceramic matrix composite material containing zirconia continuous fibers as reinforcing fibers, produced by the method according to claim 1.